Pertumbuhan Tunas Ubi Kayu (Manihot esculenta Crantz.) Genotipe Jame-jame secara In Vitro - Nugroho, Candra Catur; Khumaida, Nurul; Ardie, dan Sintho Wahyuning (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTThe continuous supply of true-to-type seedling through in vitro technique is very important for cassava (Manihot esculenta Crantz.) as the demand for seedlings is increasing. The research consisted of two experiments and they were conducted from February 2013 to February 2014. The first experiment was in vitro shoot multiplication to evaluate the effect of culture medium and single node position on growth and shoot multiplication of cassava Jame-jame genotype. This experiment was arranged in a randomized complete block design with two factors and four replications. The first factor was culture medium (MS0 and MSB3) and the second factor was single node positions used as explant (basal, middle, and top section of the stem). The result showed that middle section of the stem cultured on MS0 medium had the highest shoot height, number of leaves, and number of nodes. The second experiment was the acclimatization to evaluate the effect of culture period on the success of the acclimatization. This experiment was arranged in a completely randomized design with culture period prior to acclimatization as treatment. The results showed that seedlings from period of 12 and 24 weeks after culture showed higher survival rates (80%) than seedling from period of 36 and 48 weeks after culture (50 and 40%). Culture period prior to acclimatization had no significant effect on plant height and number of leaves.Keywords: BAP, culture period, single node position, shoot multiplication